Exploring Female Academics Underrepresentation in Senior Leadership Positions: case of Public and Private Universities in Tanzania - Murphy, Susan (My University, 2022)
Tanzania recognizes that gender equality and female empowerment are important for sustainable development of the country. The revised frameworks for EFA in the 2030 education agenda and the SDG5 give a central position to gender equality to ensure effective participation for leadership and decision making. This paper set out to comparatively examine the reasons to explain the under- representation of female academics at senior leadership positions in public and private universities in Tanzania. Although evident in Higher Education Institutions throughout the world, the specific drivers of under-representation are locally situated and context-dependent, thus requiring embedded case study analysis of institutional contexts, ethos, and progression patterns. This paper shares insight gained from forty eight (48) participants in four universities who were purposively selected from senior positions, female leaders, academic staff and university management. Interview method and Focus group discussions for data collection were employed to collect primary data and secondary data were collected through documentary review. The study used thematic analysis in data analysis. The selected Intersectionality framework guided the conduct of the study, as well as the discussion and interpretation of the findings. The data collected reveals that, cultural factors, institutional barriers and individuals’ constraints were factors that discourage female academics to senior positions in both private and public universities. The findings implied that few female academicians managed to reach senior positions and majorities are struggling to move up. Their failures were associated with traditional gender role, societal expectations, institutional ethos and harmful gender stereotypes. The study points to the need for universities to go beyond basic policy mainstreaming to support transformative understandings of equitable gender relations and norms.
ICSD
International Conference in Sustainable Development
Keywords: gender equality; leadership; higher education; Tanzania; International Development; Higher Education Policy